Bacterial Analysis and Survey of the Street Food of Kathmandu in Relation to Child Health - Tuladhar, R; Singh, Anjana (Journal of Natural History Museum, 2015)
Analysis of street foods of Kathmandu for bacterial contamination was performed in 12 different street foods. The surveillance study was carried in 200 children of primary grade from public school and 12 street vendors for the health hygiene and hazards associated with street food. Poor hygiene practice in preparation and handling of street food has been observed in the vendors. The lack of the knowledge in vendors about the source of bacterial contamination and absence of surveillance on street food has subjected street food to the high potential for food borne illness. The inadequate safety measure adopted by the targeted consumers of street food, the children, has augmented the risk associated with street food. All the food samples analyzed were contaminated with bacteria. The mesophilic count was recorded highest in Panipuri while as coliform count was highest in Chana tarkari. The least count of both was observed in Aaloo chop . Highest number of Staphylococccus aureus was found in Kerau (1.5X103cfu/g) and lowest in Momo (8.3 cfu/g). The dominant bacteria contaminating the food was S. aureus followed by Bacillus alvei, Escherichia coli, Enterobacter aerogenes, Bacillus subtilis, Serratia sp., S. saprophyticus. The contaminated hand and clothing of the person who prepare food are the major source of S. aureus. Highest percentage of E. coli found in Panipuri must be due to the use of contaminated water. Chana chatpate and Chana tarkari were the foods found to be contaminated with Salmonella sp. The type of food and the degree of hygiene practice adopted by vendor refl ects the type and magnitude of bacterial contamination. Implementation of hygienic practices in vendors may reduce the contamination of street food and health education of the school children will curtail the incidences of food borne illness. Periodical monitoring of quality of street food will avoid any future outbreaks of bacterial pathogen. J. Nat. Hist. Mus. Vol. 26, 2012: 1-9